Biblica: The Bible Atlas, a Social and Historical Journey Through the Lands of The Bible - Barry J. Beitzel; Laurie Whiddon (UK Penguin Books, 2006)
Presents one hundred twenty-five original maps showing prominent locations, journeys, battles, kingdoms, and empires discussed in the Bible and includes information on topography, geology, climate, vegetation, and key physical features of the region
pt. 6. The conquest of the kingdoms -- A people beleaguered -- The Assyrians -- The Babylonians -- The first temple destroyed -- The Persians -- Building the second temple -- Alexander the Great -- The Ptolemies -- The Seleucids -- Maccabean Jewish state -- The Romans -- pt. 7. The life of Jesus of Nazareth -- Behold the man -- The birth of Jesus -- The baptism of Jesus -- The ministry of Jesus -- Crucifixion and resurrection -- pt. 8. Spreading the word -- The gospel of truth -- The acts of the Apostles -- Paul on the road to Damascus -- The first journey of Paul -- The second journey of Paul -- The third journey of Paul -- Paul goes to Rome -- The revelation of John -- Bible reference -- Bible tables -- Bible family trees -- Bibliography -- Glossary -- Scripture references -- Gazetteer -- Index -- Picture credits
Relief shown by shading . Originally published: Lane Cove, NSW : Global Book Pub., 2006 . 1 atlas . chief consultant, Barry J. Beitzel ; [cartographer, Laurie Whiddon]
Hauppage, NY : Barron's Educational Series . Global Book Publishing (Firm)
Keywords: Biblical Studies (3ebOeGJ hOQGSGJ GdcJGH GdebOSs; Bible